Coupling Methanol Oxidation with Hydrogen Evolution on Bifunctional Co‐Doped Rh Electrocatalyst for Efficient Hydrogen Generation. (31st October 2022) - Guo, Yan; Yang, Xiaobo; Liu, Xingchen; Tong, Xili; Yang, Nianjun
Abstract: Efficient hydrogen production from electrochemical overall water splitting requires high‐performance electrocatalysts for hydrogen evolution reaction (HER) and a fast oxidation reaction to replace sluggish oxygen evolution reaction. Herein, Co‐doped Rh nanoparticles are thus grown on carbon black using Co nanosheets as the bridge. These nanoparticles with a size of ≈1.94 nm exhibit the overpotential of as low as 2 mV at 10 mA cm −2 for the HER, and a mass activity of as high as 889 mA mg −1 for the methanol oxidation reaction (MOR) in alkaline media. As confirmed by density functional theory simulations, such excellent activity originates from Co‐doping, which reduces reaction energy barriers for both the rate‐determining step of a Volmer process during the HER and the conversion of *CO to COOH* during the MOR (namely the enhanced adsorption of H2 O and COOH*). Coupling boosted HER on the cathode with accelerated MOR on the anode, efficient H2 generation is achieved. This two‐electrode cell only requires a cell voltage of 1.545 V at 10 mA cm −2 with impressive long‐life cycling stability. Such performance even outperforms that of commercial Pt/C || IrO2 cell. This study offers a new strategy to achieve efficient HER from overall water splitting. Abstract : Co‐doped Rh nanoparticles uniformly dispersed on pristine carbon black are synthesized using Co nanosheets as the bridge. Co‐Rh2 with a size of 1.94 nm exhibits outstanding electrocatalytic activity for both hydrogen evolution reaction and methanol oxidation reaction. Moreover, a two‐electrode configuration based on Co‐Rh2 catalysts only requires a cell voltage of 1.545 V to promote hydrogen generation, outperforming the benchmark Pt/C || IrO2 system.